Environmentally better positioning of industrial workshops within urban areas (Bani Malik District: Jeddah) - Alkaliwi, Rawan Mohammad; Alsulami, Morshid Mayudh (Journal of natural sciences, life and applied sciences, 2022)
The study aims to distribute industrial workshops in Bani Malik neighborhood and identify the neighborhood planning and the overlap between industrial workshops and other uses. From the industrial workshop sites standards used by the competent authorities, land is created for spatial suitability.The methodology relied on field study and comprehensive inventory method in locating workshops and their types and number, which were signed on ARCGIS program and its accessories; and therefore, a space image was used for the study area.The study concluded that the overlap of the workshops is not limited to the random side of the neighborhood, but rather the workshops overlapped with housing, schools, and hospitals in the organized part of Bani Malik3 district. Not all car service center workshops on the main street site were committed, other than light workshops and specialized centers, most of which were committed to it.All workshops of all kinds appeared strongly intertwined with other activities at a distance of less than 500 meters which claims concern for the emergence of environmental and health risksIt appears that the lands which are the most suitable for workshops of car service centers numbered only two locations on the main streets only, while the number of light workshops reached 4 sites, and the specialized centers reached 8 in different parts of the neighborhood.The reason for the small number of suitable land may be because the urban area is not compatible with the presence of industrial workshops that require large distances between them and other activities.Study recommends reorganizing industrial workshop sites according to standards in order to maintain the safety of the urban environment from the sources of industrial pollutants and work to permeate the distance of each workshop from other activities within the urban area due to the lack of sufficient spaces, and set up spaces separating the workshops from housing, schools and hospitals, to reduce interference and its problems.
Keywords: industrial workshops; residential area; overlapping industrial use; Bani Malik district; Jeddah